Province of Alberta : forest classification - Soley, H. (Alberta Department of Lands and Forests, 1957)
This map shows forest disposition in Alberta in 1957. Scale 1:1,013,760, or 16 miles to 1 inch. Relief shown by spot heights. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Shows deciduous, coniferous and mixedwood stands, also burns, brushlands, agricultural lands, First Nations reserves, Metis colonies, forest conservation areas, national parks, provincial parks, railroads, cities and towns.